Complete genome sequencing of H1N1pdm09 swine influenza isolates from Nigeria reveals likely reverse zoonotic transmission at the human-animal interface in intensive piggery. Issue 1 (1st January 2019) - Meseko, C.A.; Heidari, A.; Odaibo, G.N.; Olaleye, D.O.
ABSTRACT: Prevailing agro-ecological conditions and intermingling of human and animals in intensive farms in urban and peri-urban areas in Africa favour cross species transmission of pathogens at the human-animal interface. However, molecular epidemiology studies of zoonotic swine influenza viruses in this region are limited. In this study, isolates of pandemic influenza virus (H1N1pdm09) obtained from pigs in Nigeria were fully sequenced. BLAST of swine influenza virus genes from Nigeria was carried out in GenBank and gene alignment was done using MEGA version 7. Maximum likelihood method (PhyML program) was used to determine gene evolutionary relationships with other viruses and phylogenetic trees were constructed to infer genomic clusters and relationship. Swine influenza viruses isolated and sequenced in this study were monophyletic and 99% congenetic with human isolates from Nigeria, Cameroon, Ghana and USA suggesting reverse zoonotic transmission from humans to pigs in intensive husbandry. A Q240R and S31N substitution among others were detected in the haemagglutinin and matrix genes, respectively, indicating potentials for mutations during interspecies co-mingling and transmission. The A/H1N1pdm09 viruses circulating in pigs that are also exposed to avian influenza in the same epidemiological zones could engender emergence of novel viruses with zoonotic or pandemic potential requiring enhanced surveillance and monitoring.